Structured Systems Analysis / Tools and Techniques - Gane Chris; Sarson Trish (Prentice Hall)
Preface, The Need for Better Tools, What the Tools are and How They Fit Together, Drawing Data Flow Diagrams, Building and Using a Data Dictionary, Analyzing and Presenting Process Logic, Defining the Contents of Data Stores, Analyzing Response Requirements, Using the Tools: A Structured Methodology, Deriving a Structured Design from the Logical Model, Introducing Structured Systems Analysis into Your Organization, Glossary, Index.